The Influence of Socio-Economic Status, and Tutoring on Student Achievement in Economics Subjects in High School - Cahyo Adhi, Dwi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine the effect of socio-economic status on student achievement in economics class XI IPS program at SMAN 1 Jogonalan, to determine the effect of tutoring on student achievement in Economics class XI social studies program at SMAN 1 Jogonalan, and to determine the effect socio-economic status and tutoring on student achievement in economics class XI social studies program at SMAN 1 Jogonalan. Methodology: This study was an ex-post facto study. The variables of this study were economic achievement, socioeconomic status, and tutoring. The population in this study were 109 students of class XI IPS at SMAN 1 Jogonalan in the academic year 2014/2015 as many as 109. Collection technique data using questionnaires and documentation. The analytical method used is multiple regression analysis. Main findings: (1) socio-economic status does not have a positive effect on economic achievement as indicated by a sig value of 0.063 more than 0.05. (2) tutoring has a positive effect on economics learning achievement as indicated by a sig value of 0.000 less than 0.05. (3) socio-economic status and tutoring have a positive effect on economics learning achievement as indicated by a sig value of 0.000 less than 0.05. The R2 value of 0.238 means that 23.8% of Economics learning achievement is explained by socioeconomic status and tutoring. While 76.2% is explained by other factors not examined in this study. Novelty/Originality of this research: This research can provide an explanation regarding the influence of socioeconomic status, and tutoring on student achievement in economics subjects.